2011
DOI: 10.2217/nnm.10.162
|View full text |Cite
|
Sign up to set email alerts
|

Submicron Polymer Particles Containing Fluorescent Semiconductor Nanocrystals Cdse/Zns for Bioassays

Abstract: The obtained fluorescent particles sensitized by anti-Yersinia pestis antibodies were used for rapid agglutination glass test suitable for screening analysis of Y. pestis antigen and for microtiter particle agglutination, which, owing to its speed and simplicity, is very beneficial for diagnostic detection of Y. pestis antigen. Recombinant 4D5 scFv antibodies designed and conjugated with polymer particles containing quantum dots provide multipoint highly specific binding with cancer marker HER2/neu on the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…Previous studies on cell cultures showed that it is suitable for the preparation of self assembling magnetofluorescent complexes [13,29], nanodiamonds [30], up converting nanoparticles [31,32], and polymeric nanoparticles [33]. The use of molecular adaptors noncovalently interacting with each other with high affinity and specificity makes it possible to readily replace one visualizing/targeting module for another without resorting to the adapta tion of the conjugation method.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on cell cultures showed that it is suitable for the preparation of self assembling magnetofluorescent complexes [13,29], nanodiamonds [30], up converting nanoparticles [31,32], and polymeric nanoparticles [33]. The use of molecular adaptors noncovalently interacting with each other with high affinity and specificity makes it possible to readily replace one visualizing/targeting module for another without resorting to the adapta tion of the conjugation method.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the difference of fluorescence signal at different pH became higher after modifications. It is worth noting that fluorescence of the polymer particles doped with QDs by swelling procedure, prepared in accordance with [4], practically was not changed under pH variation (Fig. 5).…”
Section: Ph-dependent Optical Properties Of the Polymer Particlesmentioning
confidence: 89%
“…There are descriptions of different approaches for incorporation of these fluorescent labels inside the colloid polymer particles in the literature; such as the entrapment of QDs by swelling of polymer particles [4], controlled precipitation [5], heterocoagulation via electrostatic-driven interactions [6] or thiol-bond formation [7]. Further significant challenge in fluorescent particle production, however, is closely related to flexible methods that lead to creation of polymer particles with outer QD loading.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, directed coupling of an anticreatine kinase antibody in a commercial EIA system resulted in a shorter assay time and improved assay performance over use ofthe uncomplexed antibody [213]. Antibody fragments have even been conjugated to QD-containing polyacrolein and poly(acrolein-costyrene) particles by reaction with surface aldehyde groups [214].In the case of whole immunoglobulins, these were usedin vitro in a simple and rapid agglutination-based detection of the pathogenic bacterium Yersinia pestis, while similarly conjugated anti-HER2 scFvs proved suitable for use in multipoint detection of cells expressing the cancer marker [215].…”
Section: In Vitro Applicationsmentioning
confidence: 99%